Hard carbon material, preparation method and application thereof, and sodium ion battery

By heat treatment of biomass carbon source and mixed molten salt and surface coating with coating agent, the hard carbon material obtained by carbonization treatment is finally solved, and the electrochemical performance of sodium ion batteries prepared by existing hard carbon materials is solved. The poor problem has achieved high sodium storage capacity and excellent first-term effect, and has low cost and green environmental protection.

CN119461326APending Publication Date: 2025-02-18SHANGHAI SHANSHAN NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411651861.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The electrochemical performance of sodium ion batteries prepared by existing hard carbon materials is poor, with low capacity and low first-week Coulomb efficiency, and it is difficult to take into account both the first-week Coulomb efficiency and capacity.

Method used

The biomass carbon source and mixed molten salt are heat treated to generate porous carbon, and then surface coated by coating agent is carried out, and finally hard carbon material with suitable pore size distribution, closed pore volume and specific surface area are obtained through carbonization.

Benefits of technology

It realizes high sodium storage capacity and excellent first effect of hard carbon materials in sodium ion batteries. The charging capacity can reach more than 330 mAh/g, and the first effect can reach more than 88.8%. At the same time, the process is low-cost, green and environmentally friendly, and easy to scale. Production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461326A_ABST
    Figure CN119461326A_ABST
Patent Text Reader

Abstract

The invention discloses a hard carbon material, a preparation method and application thereof and a sodium ion battery. The preparation method of the hard carbon material comprises the following steps: S1, mixing a biomass carbon source and mixed molten salt to obtain a mixture, and carrying out heat treatment on the mixture to obtain porous carbon; the mixed molten salt at least comprises two kinds of molten salt; s2, carrying out surface coating treatment on the porous carbon by adopting a coating agent to obtain a hard carbon precursor; and S3, carrying out carbonization treatment on the hard carbon precursor to obtain the hard carbon material. The obtained hard carbon material has proper pore size distribution, closed pore volume and specific surface area, has excellent electrochemical performance when being applied to the sodium ion battery, and can simultaneously take both high sodium storage capacity and excellent first effect into account. Moreover, the preparation method is low in cost, green and environment-friendly, and large-scale production is easy to realize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hard carbon material, a preparation method thereof, an application thereof and a sodium ion battery. Background Art

[0002] With the increasing demand for renewable energy to replace traditional fossil fuels and related large-scale energy storage systems (EES), battery technology and applications have developed rapidly. Lithium-ion batteries (LIBs) have developed rapidly in the portable electronics market and expanded to EES applications due to their high energy density, no memory effect, and long life. However, the content of lithium in the earth's crust is very low, and large-scale demand forces us to find new alternatives. Sodium-ion batteries (SIBs) have become an ideal alternative to lithium-ion batteries because sodium ions have similar physicochemical properties to lithium ions and higher crustal reserves. In terms of comprehensive consideration of cost, performance, and resource sustainability, hard carbon has been proven to be the most favorable choice for negative electrode materials. Generally, hard carbon materials are composed of many disordered, stacked, and curved graphene sheets. These graphene sheets contain a large number of defects, and the curved graphene sheets are stacked to form closed pores. At present, the electrochemical performance of sodium-ion batteries prepared from hard carbon materials is poor, with low capacity, low first-cycle coulombic efficiency, and it is difficult to balance the first-cycle coulombic efficiency and capacity at the same time.

[0003] The closed pores formed in hard carbon materials provide ample space for the storage of sodium ions. This "pore filling" mechanism makes the platform capacity of hard carbon at low potential account for 50% to 80% of the total capacity. Therefore, the microstructure of hard carbon materials, especially the design of pore structure, is an effective way to improve the low-potential platform capacity and enhance the sodium ion storage performance. Some existing pore structure design strategies, such as chemical activation and template agents, can effectively increase the volume of closed pores in disordered carbon materials and enhance the stability of carbonaceous precursors. Commonly used chemical activators and template agents include ZnO, MgO, K 2 CO3 or KOH, etc., which can effectively increase the number and pore size of closed pores in hard carbon. However, these chemicals inevitably cause some problems, including high cost, equipment corrosion and environmental pollution. Although the sodium ion storage capacity of sodium ion batteries in the low voltage platform area has been greatly enhanced, it is impossible to produce hard carbon materials in a low-cost and green process, and the resulting sodium ion batteries cannot take into account both high sodium storage capacity and excellent first efficiency. Summary of the invention

[0004] In order to solve the problem that sodium ion batteries obtained by using existing hard carbon materials cannot take into account both high sodium storage capacity and excellent first efficiency, the present invention provides a hard carbon material and a preparation method, application and sodium ion battery thereof. The hard carbon material prepared by the present invention has a suitable pore size distribution, closed pore volume and specific surface area, and when applied to sodium ion batteries, it can take into account both high sodium storage capacity and excellent first efficiency.

[0005] To achieve the above objectives, the present invention adopts the following technical solutions.

[0006] The present invention provides a method for preparing a hard carbon material, which comprises the following steps:

[0007] S1. Mixing a biomass carbon source and a mixed molten salt to obtain a mixture, and heat-treating the mixture to obtain porous carbon; wherein the mass ratio of the biomass carbon source to the mixed molten salt is 1:(1-30); and the mixed molten salt contains at least two molten salts;

[0008] S2, using a coating agent to perform surface coating treatment on the porous carbon to obtain a hard carbon precursor; wherein the mass ratio of the porous carbon to the coating agent is 1: (0.05-0.3);

[0009] S3, carbonizing the hard carbon precursor to obtain a hard carbon material.

[0010] In step S1, the specific surface area of ​​the porous carbon may be 100-1500 m 2 / g, preferably 200~1000 m 2 / g, for example, 328.4 m 2 / g, 389.3 m 2 / g, 420.6 m 2 / g, 455.7 m 2 / g, 489.6 m 2 / g or 620.5 m 2 / g.

[0011] In step S1, the micropore specific surface area of ​​the porous carbon may be 50-600 m 2 / g, preferably 100~500 m 2 / g, for example 257.2 m 2 / g, 316.3 m 2 / g, 323.4 m 2 / g, 350.6 m 2 / g, 405.4 m 2 / g or 480.8 m 2 / g.

[0012] In step S1, the micropore volume of the porous carbon may be 0.10-0.60 cm 3 / g, preferably 0.10~0.5 cm 3 / g, for example 0.20 cm 3 / g, 0.24cm 3 / g, 0.25 cm 3 / g, 0.28cm 3 / g, 0.30 cm 3 / g or 0.35cm 3 / g.

[0013] In step S1, the average pore size of the porous carbon may be 1.50-3.0 nm, preferably 2.0-2.5 nm, for example, 2.13 nm, 2.17 nm, 2.18 nm, 2.25 nm, 2.27 nm or 2.38 nm.

[0014] In step S1, the tap density of the porous carbon may be 0.25-0.70 g / cm 3 , preferably 0.30~0.60 g / cm 3 , for example 0.38 g / cm 3 , 0.44 g / cm 3 , 0.47 g / cm 3 , 0.50 g / cm 3 , 0.51 g / cm 3 or 0.55 g / cm 3 .

[0015] In step S1, the biomass carbon source can be selected from one or more of coconut shells, walnut shells, fruit shells, coffee grounds, sawdust, lignin, tea stems and bamboo, such as coconut shells.

[0016] In step S1, before the mixing, the biomass carbon source may be pretreated. Preferably, the pretreatment step includes washing, drying and crushing.

[0017] The cleaning may be a conventional cleaning method in the art. Preferably, the cleaning is performed by mechanical stirring. Preferably, the cleaning is performed by stirring and washing with deionized water. Preferably, the cleaning further includes a filtering step.

[0018] The drying device may be a device conventionally used for drying in the art, preferably an air drier, a vacuum drier or a single cone drier, for example, an air drier.

[0019] In some embodiments, the drying temperature of the air drier is preferably 80-120°C, more preferably 90-110°C, for example 105°C.

[0020] In some embodiments, the drying time of the air dryer is preferably 5 to 20 hours, more preferably 8 to 12 hours, for example 8 hours, 10 hours or 12 hours.

[0021] The pulverizing equipment may be equipment conventionally used for pulverizing in the art, preferably a roller mill, a mechanical mill, a jet mill or a cryogenic mill, such as a jet mill.

[0022] In the present invention, the mixed molten salt refers to a molten salt mixture formed by at least two molten salts, and the amounts of different molten salts in the mixed molten salt may be the same or different.

[0023] In step S1, the mixed molten salt can be selected from at least two of lithium chloride, sodium chloride, potassium chloride, cesium chloride, calcium chloride and magnesium chloride, for example, sodium chloride / potassium chloride, calcium chloride / sodium chloride, potassium chloride / lithium chloride or sodium chloride / cesium chloride.

[0024] In some preferred embodiments, in step S1, the mixed molten salt includes molten salt A and molten salt B; the molten salt A is lithium chloride, sodium chloride or calcium chloride; the molten salt B is potassium chloride or sodium chloride; the molten salt A and the molten salt B are of different types.

[0025] The molar ratio of the molten salt A to the molten salt B is preferably 1:(0.2-5), more preferably 1:(0.5-5), for example 1:0.7, 1:1 or 1:2.

[0026] In some specific embodiments, the molten salt A is lithium chloride, and the molten salt B is potassium chloride; the molar ratio of the lithium chloride to the potassium chloride is 1:0.7.

[0027] In some specific embodiments, the molten salt A is lithium chloride, and the molten salt B is potassium chloride; the molar ratio of the lithium chloride to the potassium chloride is 1:1.

[0028] In some specific embodiments, the molten salt A is sodium chloride, and the molten salt B is potassium chloride; the molar ratio of the sodium chloride to the potassium chloride is 1:1.

[0029] In some specific embodiments, the molten salt A is calcium chloride, and the molten salt B is sodium chloride; the molar ratio of the calcium chloride to the sodium chloride is 1:2.

[0030] In step S1, the mass ratio of the biomass carbon source to the mixed molten salt is preferably 1:(5-30), such as 1:10 or 1:20.

[0031] In step S1, the mixing device may be a device conventionally used for mixing in the art, such as a ball mill.

[0032] The rotation speed of the ball mill is preferably 300-800 r / min, for example, 400 r / min, 450 r / min or 500 r / min.

[0033] The ball milling time is preferably 0.5-10 h, for example 0.5 h, 1 h or 2 h.

[0034] In step S1, the heat treatment is preferably performed by pre-carbonization.

[0035] The pre-carbonization temperature is preferably 400-800°C, such as 600°C, 700°C or 800°C.

[0036] The pre-carbonization time is preferably 1 to 5 hours, such as 2 hours, 3 hours or 4 hours.

[0037] The heating rate of the pre-carbonization may be the heating rate of the pre-carbonization conventionally performed in the art, preferably 1-5°C / min, for example 2°C / min, 3°C / min or 5°C / min.

[0038] In step S1, the heat treatment is preferably performed under an inert atmosphere, wherein the inert atmosphere preferably includes an inert gas and / or nitrogen, such as nitrogen; the inert gas is, for example, argon.

[0039] In step S1, the heat treatment preferably further includes washing and drying.

[0040] Wherein, the washing is preferably water washing. The water washing can be a conventional water washing step in the art. The water washing method preferably adopts mechanical stirring. Preferably, the water washing further includes filtering and collecting filter residues. Wherein, the filtration can be a conventional filtration step in the art. The filtration is generally vacuum filtration or filter press.

[0041] The drying equipment may be conventional in the art, such as a blast dryer, a vacuum dryer, a single cone dryer, etc., preferably a blast dryer. The drying temperature of the blast dryer may be 80-120°C, preferably 90-110°C, and more preferably 105°C. The drying time of the blast dryer may be 5-20h, preferably 8-12h, such as 8h, 10h or 12h.

[0042] Wherein, after the drying, the step of evaporating the solution is preferably further included. Wherein, the temperature of evaporating the solution is preferably 60-110° C., such as 70° C., 80° C. or 90° C. Wherein, the absolute pressure of evaporating the solution is preferably 20-101 kPa, such as 30 kPa, 50 kPa or 70 kPa.

[0043] In step S2, the mass ratio of the porous carbon to the coating agent is preferably 1:(0.15-0.3), for example, 1:0.20 or 1:0.25.

[0044] In step S2, the surface coating treatment may be conventional in the art, and generally includes the following steps: mixing the coating agent with the porous carbon.

[0045] The mixing may be conventional in the art, and is generally carried out in a fusion machine.

[0046] Wherein, the rotation speed of the fusion machine is preferably 200-800 r / min, such as 300 r / min, 350 r / min or 400 r / min.

[0047] In step S2, the coating agent preferably includes one or more of phenolic resin, epoxy resin, petroleum resin and polyester resin; the coating agent is, for example, phenolic resin. The phenolic resin preferably includes thermosetting phenolic resin and / or thermoplastic phenolic resin.

[0048] In some embodiments, the coating agent is a thermosetting phenolic resin, which is a liquid and satisfies the following conditions: viscosity of 20 to 50 cp, moisture content ≤0.5%, ash content ≤0.1%, residual carbon value of 15% to 30%, free phenol content ≤1.5%, and the percentage is the mass percentage of the thermosetting phenolic resin.

[0049] In some embodiments, the coating agent is a thermoplastic phenolic resin; when the thermoplastic phenolic resin is solid, the method further comprises mixing the thermoplastic phenolic resin with a solvent to form a liquid mixture.

[0050] The solvent may be a conventional solvent in the art that can completely dissolve the thermoplastic phenolic resin, preferably one or more of an alcohol solvent, a ketone solvent and a benzene solvent, more preferably an alcohol solvent; the alcohol solvent is, for example, an ethanol solvent.

[0051] The mass ratio of the thermoplastic phenolic resin to the solvent is preferably (0.1-2):1, such as 0.2:1 or 0.3:1.

[0052] The step of mixing the thermoplastic phenolic resin and the solvent may be a conventional mixing step in the art, and preferably includes the following steps: mixing the two by mechanical stirring until they are uniformly dissolved.

[0053] The thermoplastic phenolic resin is preferably a linear phenolic resin; the linear phenolic resin is preferably selected from one or more of phenol formaldehyde resin, resorcinol formaldehyde resin, m-aminophenol formaldehyde resin, phenolic epoxy resin and benzoxazine resin, such as phenol formaldehyde resin.

[0054] The thermoplastic phenolic resin preferably meets the following conditions: softening point of 80-120° C., ash content ≤0.1%, moisture content ≤0.5%, residual carbon value 40%-70%, where the percentages are the mass percentages of the thermoplastic phenolic resin.

[0055] In step S3, the temperature of the carbonization treatment is preferably 1100-1500°C, such as 1200°C, 1300°C or 1400°C.

[0056] In step S3, the carbonization treatment time is preferably 1 to 4 hours, for example, 2 hours, 3 hours or 4 hours.

[0057] In step S3, the heating rate of the carbonization treatment is preferably 1-10°C / min, preferably 1°C / min, 2°C / min, 3°C / min or 5°C / min.

[0058] In step S3, the carbonization treatment is preferably carried out under an inert atmosphere. The inert atmosphere refers to an atmosphere formed by a gas that does not react with the raw material during heat treatment, and is not limited to an atmosphere formed by an inert gas. The inert atmosphere preferably includes an inert gas and / or nitrogen, such as nitrogen. The inert gas is, for example, argon.

[0059] In step S3, the carbonization treatment preferably adopts a staged heating method, and the staged heating method preferably includes the following steps: first heating to 500-700°C at a heating rate of 2-10°C / min, keeping the temperature constant for 1-4 hours, and then heating to 1100-1500°C at a heating rate of 1-5°C / min, and keeping the temperature constant for 1-4 hours.

[0060] In step S3, the equipment for the carbonization treatment is preferably a pit furnace, a rotary kiln, a tube furnace, a box furnace, a tunnel kiln, a vacuum furnace, a push plate kiln or a roller kiln.

[0061] The present invention provides a hard carbon material prepared by adopting the preparation method of the hard carbon material.

[0062] In the present invention, the specific surface area of ​​the hard carbon material can be 1 to 20 m 2 / g, preferably 2~10 m 2 / g, for example 2.5m 2 / g, 3.0 m 2 / g, 3.4 m 2 / g, 3.7 m2 / g, 3.9 m 2 / g or 4.7 m 2 / g.

[0063] In the present invention, the hard carbon material has a rich microporous structure, and the average pore size of the hard carbon material may be 0.3-1.5 nm, preferably 0.4-1.0 nm, such as 0.53 nm or 0.88 nm.

[0064] In the present invention, the median particle size Dv50 of the hard carbon material may be 4 to 10 μm, preferably 5 to 7 μm, such as 5.4 μm, 5.6 μm, 5.7 μm, 6.0 μm or 6.1 μm.

[0065] In the present invention, the true density of the hard carbon material can be 1.3-1.5 g / cm 3 , for example 1.31 g / cm 3 , 1.32 g / cm 3 , 1.33 g / cm 3 , 1.34g / cm 3 , 1.35 g / cm 3 or 1.36 g / cm 3 .

[0066] In the present invention, the tap density of the hard carbon material can be 0.5-0.9 g / cm 3 , preferably 0.6~0.8 g / cm 3 , for example 0.74 g / cm 3 , 0.76g / cm 3 , 0.77 g / cm 3 , 0.78 g / cm 3 or 0.80 g / cm 3 .

[0067] In the present invention, the closed pore volume of the hard carbon material may be 0.27-0.35 cm 3 / g, for example, 0.287 cm 3 / g, 0.293 cm 3 / g, 0.298 cm 3 / g, 0.304 cm 3 / g, 0.309 cm 3 / g, 0.315 cm 3 / g, 0.321 cm 3 / g, 0.327cm 3 / g or 0.333 cm 3 / g.

[0068] In the present invention, preferably, the hard carbon material comprises a porous carbon core, and amorphous carbon is arranged on the surface and in the pores of the porous carbon core.

[0069] The present invention provides an application of the hard carbon material as described above as a negative electrode material in a sodium ion battery.

[0070] The present invention also provides a sodium ion battery, which comprises the hard carbon material as described above.

[0071] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0072] The reagents and raw materials used in the present invention are commercially available.

[0073] The positive and progressive effects of the present invention are:

[0074] In the preparation method of the hard carbon material of the present invention, a mixed molten salt is used to form pores in the biomass carbon source, and a coating agent is used for surface coating treatment. The obtained hard carbon material has a suitable pore size distribution, closed pore volume and specific surface area. When it is applied to sodium ion batteries, it can take into account both high sodium storage capacity and excellent first efficiency. Specifically, the charging capacity of the sodium ion battery containing it can reach more than 330 mAh / g, and even more than 370 mAh / g; and taking into account the excellent first efficiency, specifically more than 88.8%. Moreover, the preparation process is low-cost, green and environmentally friendly, and easy to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 This is a pore size distribution diagram of the hard carbon material obtained in Example 1 of the present invention.

[0076] Figure 2 This is a SEM image of the hard carbon precursor obtained in Example 1 of the present invention.

[0077] Figure 3 This is a SEM image of the hard carbon material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0078] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0079] Example 1

[0080] (1) Preparation of hard carbon materials:

[0081] S0, soaking the biomass coconut shell raw material in deionized water, mechanically stirring for 2 hours to wash to remove dust adsorbed on the surface, and then performing solid-liquid separation on the above-mentioned feed liquid by normal pressure filtration, placing the obtained solid coconut shell filter cake material in a blast dryer at 105° C. and drying it for 12 hours, and after drying, crushing the obtained coconut shell material by a jet mill to obtain crushed coconut shell;

[0082] S1-1, according to the mass ratio of crushed coconut shell to mixed molten salt being 1:10, crushed coconut shell and lithium chloride / potassium chloride mixed molten salt (molar ratio being 1:0.7) were mixed by ball mill at 400 r / min for 2 h to obtain a mixture;

[0083] S1-2, placing the above-mentioned mixed material in a carbonization furnace, under nitrogen protection conditions, heating the temperature to 700°C at a rate of 2°C / min and keeping it warm for 3 hours for pre-carbonization, discharging the material after it naturally cools down to room temperature, and then soaking the material in deionized water, mechanically stirring for 2 hours to wash to remove the molten salt, and obtaining a liquid feed; then the liquid feed is subjected to solid-liquid separation by normal pressure filtration, and the obtained filter cake material is placed in a blast dryer and dried at 105°C for 12 hours to obtain porous carbon; the obtained filtrate is subjected to solution evaporation under the conditions of an absolute pressure of 30 kPa and an evaporation temperature of 70°C, and the obtained solid is the recovered molten salt;

[0084] S2, porous carbon and thermosetting phenolic resin (residual carbon value is 23%, viscosity is 35 cp) are mixed in a fusion machine at a mass ratio of 1:0.15 at a speed of 300 r / min for 30 minutes to obtain a hard carbon precursor;

[0085] S3. Place the hard carbon precursor in a carbonization furnace. Under nitrogen protection, heat the temperature to 700°C at a rate of 3°C / min and keep it for 2 h. Then heat the temperature to 1400°C at a rate of 2°C / min and keep it for 2 h for carbonization. After naturally cooling to room temperature, discharge the material to obtain a hard carbon material.

[0086] (2) Preparation of sodium ion batteries:

[0087] The prepared hard carbon material was used as the negative electrode material. The negative electrode material, the conductive agent Super P, and the binder PVDF were weighed, ground and mixed according to a mass ratio of 90:5:5 (a total of 100 parts by mass). NMP was used as a solvent to mix and prepare a viscous uniform slurry (the slurry solid content was 40%~50%). The slurry was then coated on the copper foil by a doctor blade method. The coated copper foil was then placed in a vacuum oven at 80°C and dried for 12 h. The dried copper foil was cut into 2 cm 2At room temperature, a sodium metal sheet was used as the counter electrode, the electrode prepared above was used as the working electrode, a GE Whatman glass fiber diaphragm was used as the diaphragm, and a 1 mol / L NaPF 6 / EC+DMC (volume ratio of 1:1) solution was used as the electrolyte, and button-type sodium-ion batteries were assembled in a vacuum glove box and tightly mechanically sealed.

[0088] Example 2

[0089] (1) Preparation of hard carbon materials:

[0090] S0, soaking the biomass coconut shell raw material in deionized water, mechanically stirring for 2 hours to wash to remove dust adsorbed on the surface, and then performing solid-liquid separation on the above-mentioned feed liquid by normal pressure filtration, placing the obtained solid coconut shell filter cake material in a blast dryer at 105° C. and drying it for 12 hours, and after drying, crushing the obtained coconut shell material by a jet mill to obtain crushed coconut shell;

[0091] S1-1, according to the mass ratio of crushed coconut shell to mixed molten salt being 1:15, crushed coconut shell and lithium chloride / potassium chloride mixed molten salt (molar ratio being 1:1) were mixed by ball mill at 450 r / min for 1 h to obtain a mixture;

[0092] S1-2, placing the above-mentioned mixed material in a carbonization furnace, under nitrogen protection conditions, heating the temperature to 600°C at a rate of 3°C / min and keeping it warm for 4 hours for pre-carbonization, discharging the material after it is naturally cooled to room temperature, and then soaking the material in deionized water, mechanically stirring for 2 hours to wash to remove the molten salt, and obtaining a liquid feed; then the liquid feed is subjected to solid-liquid separation by normal pressure filtration, and the obtained precursor filter cake material is placed in a blast dryer and dried at 105°C for 12 hours to obtain porous carbon; the obtained filtrate is subjected to solution evaporation under the conditions of an absolute pressure of 50 kPa and an evaporation temperature of 80°C, and the obtained solid is the recovered molten salt;

[0093] S2, porous carbon and thermosetting phenolic resin (residual carbon value is 27%, viscosity is 40 cp) are mixed in a fusion machine at a speed of 350 r / min for 20 min according to a mass ratio of 1:0.20 to obtain a hard carbon precursor;

[0094] S3. Place the hard carbon precursor in a carbonization furnace. Under nitrogen protection, heat the temperature to 600°C at a rate of 2°C / min and keep it warm for 3 h. Then heat the temperature to 1300°C at a rate of 1°C / min and keep it warm for 3 h for carbonization. After naturally cooling to room temperature, discharge the material to obtain a hard carbon material.

[0095] (2) Preparation of sodium ion battery: The specific steps are the same as those in Example 1.

[0096] Example 3

[0097] (1) Preparation of hard carbon materials:

[0098] S0, soaking the biomass coconut shell raw material in deionized water, mechanically stirring for 2 hours to wash to remove dust adsorbed on the surface, and then performing solid-liquid separation on the above-mentioned feed liquid by normal pressure filtration, placing the obtained solid coconut shell filter cake material in a blast dryer at 105° C. and drying it for 12 hours, and after drying, crushing the obtained coconut shell material by a jet mill to obtain crushed coconut shell;

[0099] S1-1, according to the mass ratio of crushed coconut shell to mixed molten salt being 1:20, crushed coconut shell and sodium chloride / potassium chloride mixed molten salt (molar ratio being 1:1) were mixed by a ball mill at 400 r / min for 0.5 h to obtain a mixture;

[0100] S1-2, placing the above-mentioned mixed material in a carbonization furnace, under nitrogen protection conditions, heating the temperature to 800°C at a rate of 5°C / min and keeping it warm for 2 hours for pre-carbonization, discharging the material after it is naturally cooled to room temperature, and then soaking the material in deionized water, mechanically stirring for 2 hours to wash to remove the molten salt, and obtaining a liquid feed; then the liquid feed is subjected to solid-liquid separation by normal pressure filtration, and the obtained precursor filter cake material is placed in a blast dryer and dried at 105°C for 12 hours to obtain porous carbon; the obtained filtrate is subjected to solution evaporation under the conditions of an absolute pressure of 70 kPa and an evaporation temperature of 90°C, and the obtained solid is the recovered molten salt;

[0101] S2, porous carbon and thermosetting phenolic resin (residual carbon value is 20%, viscosity is 30 cp) () according to the mass ratio of 1:0.25, the material is mixed in a fusion machine at a speed of 400r / min for 10min to obtain a hard carbon precursor;

[0102] S3. Place the hard carbon precursor in a carbonization furnace. Under nitrogen protection, heat the temperature to 700°C at a rate of 5°C / min and keep it for 2 h. Then heat the temperature to 1200°C at a rate of 3°C / min and keep it for 4 h for carbonization. After naturally cooling to room temperature, discharge the material to obtain a hard carbon material.

[0103] (2) Preparation of sodium ion battery: The specific steps are the same as those in Example 1.

[0104] Example 4

[0105] (1) Preparation of hard carbon materials:

[0106] S0, soaking the biomass coconut shell raw material in deionized water, mechanically stirring for 2 hours to wash to remove dust adsorbed on the surface, and then performing solid-liquid separation on the above-mentioned feed liquid by normal pressure filtration, placing the obtained solid coconut shell filter cake material in a blast dryer at 105° C. and drying it for 12 hours, and after drying, crushing the obtained coconut shell material by a jet mill to obtain crushed coconut shell;

[0107] S1-1, according to the mass ratio of crushed coconut shell to mixed molten salt being 1:15, crushed coconut shell and calcium chloride / sodium chloride mixed molten salt (molar ratio being 1:2) were mixed by ball mill at 450 r / min for 1 h to obtain a mixture;

[0108] S1-2, placing the above-mentioned mixed material in a carbonization furnace, under nitrogen protection conditions, heating the temperature to 700°C at a rate of 2°C / min and keeping it warm for 4 hours for pre-carbonization, discharging the material after it naturally cools down to room temperature, and then soaking the material in deionized water, mechanically stirring for 2 hours to wash to remove the molten salt, and obtaining a liquid feed; then the liquid feed is subjected to solid-liquid separation by normal pressure filtration, and the obtained precursor filter cake material is placed in a blast dryer and dried at 105°C for 12 hours to obtain porous carbon; the obtained filtrate is subjected to solution evaporation under the conditions of an absolute pressure of 50 kPa and an evaporation temperature of 80°C, and the obtained solid is the recovered molten salt;

[0109] S2, mixing porous carbon and thermosetting phenolic resin (residual carbon value of 18%, viscosity of 20 cp) in a mass ratio of 1:0.25 in a fusion machine at a speed of 400 r / min for 10 min to obtain a hard carbon precursor;

[0110] S3. Place the hard carbon precursor in a carbonization furnace. Under nitrogen protection, heat the temperature to 700°C at a rate of 3°C / min and keep it for 2 h. Then heat the temperature to 1200°C at a rate of 1°C / min and keep it for 3 h for carbonization. After naturally cooling to room temperature, discharge the material to obtain a hard carbon material.

[0111] (2) Preparation of sodium ion battery: The specific steps are the same as those in Example 1.

[0112] Example 5

[0113] (1) Preparation of hard carbon materials:

[0114] S0, soaking the purchased biomass coconut shell raw material in deionized water, mechanically stirring for 2 hours to wash to remove dust adsorbed on the surface, and then performing solid-liquid separation on the above-mentioned feed liquid by normal pressure filtration, placing the obtained solid coconut shell filter cake material in a blast dryer at 105° C. and drying for 12 hours, and after drying, crushing the obtained coconut shell material by a jet mill to obtain crushed coconut shell;

[0115] S1-1, according to the mass ratio of crushed coconut shell to mixed molten salt being 1:5, crushed coconut shell and lithium chloride / potassium chloride mixed molten salt (molar ratio being 1:1) were mixed by ball mill at 400 r / min for 2 h to obtain a mixture;

[0116] S1-2, placing the above-mentioned mixed material in a carbonization furnace, under nitrogen protection conditions, heating the temperature to 700°C at a rate of 2°C / min and keeping it warm for 3 hours for pre-carbonization, discharging the material after it is naturally cooled to room temperature, and then soaking the material in deionized water, mechanically stirring for 2 hours to wash to remove the molten salt, and obtaining a liquid feed; then the liquid feed is subjected to solid-liquid separation by normal pressure filtration, and the obtained precursor filter cake material is placed in a blast dryer and dried at 105°C for 12 hours to obtain porous carbon; the obtained filtrate is subjected to solution evaporation under the conditions of an absolute pressure of 30 kPa and an evaporation temperature of 70°C, and the obtained solid is the recovered molten salt;

[0117] S2-1, thermoplastic phenol formaldehyde resin (residual carbon value of 45%, softening point of 110°C) and ethanol solvent are mixed in a mass ratio of 0.3:1 by mechanical stirring until the two are uniformly dissolved to obtain an alcohol solution of the resin;

[0118] S2-2, the porous carbon and the alcohol solution of the above resin are mixed in a fusion machine at a mass ratio of 1:0.20 at a speed of 300 r / min for 30 minutes to obtain a hard carbon precursor;

[0119] S3. Place the hard carbon precursor in a carbonization furnace. Under nitrogen protection, heat the temperature to 700°C at a rate of 3°C / min and keep it warm for 3 h. Then heat the temperature to 1300°C at a rate of 2°C / min and keep it warm for 4 h for carbonization. After naturally cooling to room temperature, discharge the material to obtain the hard carbon material.

[0120] (2) Preparation of sodium ion battery: The specific steps are the same as those in Example 1.

[0121] Example 6

[0122] (1) Preparation of hard carbon materials:

[0123] S0, soaking the biomass coconut shell raw material in deionized water, mechanically stirring for 2 hours to wash to remove dust adsorbed on the surface, and then performing solid-liquid separation on the above-mentioned feed liquid by normal pressure filtration, placing the obtained solid coconut shell filter cake material in a blast dryer at 105° C. and drying it for 12 hours, and after drying, crushing the obtained coconut shell material by a jet mill to obtain crushed coconut shell;

[0124] S1-1, according to the mass ratio of crushed coconut shell to mixed molten salt being 1:5, crushed coconut shell and lithium chloride / potassium chloride mixed molten salt (the molar ratio of the two is 1:1) are mixed by ball mill at 400r / min for 2h to obtain a mixture;

[0125] S1-2, placing the above-mentioned mixed material in a carbonization furnace, under nitrogen protection conditions, heating the temperature to 700°C at a rate of 2°C / min and keeping it warm for 3 hours for pre-carbonization, discharging the material after it is naturally cooled to room temperature, and then soaking the material in deionized water, mechanically stirring for 2 hours to wash to remove the molten salt, and obtaining a liquid feed; then the liquid feed is subjected to solid-liquid separation by normal pressure filtration, and the obtained precursor filter cake material is placed in a blast dryer and dried at 105°C for 12 hours to obtain porous carbon; the obtained filtrate is subjected to solution evaporation under the conditions of an absolute pressure of 30 kPa and an evaporation temperature of 70°C, and the obtained solid is the recovered molten salt;

[0126] S2-1, thermoplastic phenol formaldehyde resin (residual carbon value is 60%, softening point is 110°C) and ethanol solvent are mixed in a mass ratio of 0.2:1 by mechanical stirring until the two are uniformly dissolved to obtain an alcohol solution of the resin;

[0127] S2-2, mixing the porous carbon and the alcohol solution of the above resin in a mass ratio of 1:0.15 in a fusion machine at a speed of 350 r / min for 1 h to obtain a hard carbon precursor;

[0128] S3. Place the hard carbon precursor in a carbonization furnace. Under nitrogen protection, heat the temperature to 700°C at a rate of 3°C / min and keep it warm for 3 h. Then heat the temperature to 1400°C at a rate of 3°C / min and keep it warm for 4 h for carbonization. After naturally cooling to room temperature, discharge the material to obtain the hard carbon material.

[0129] (2) Preparation of sodium ion battery: The specific steps are the same as those in Example 1.

[0130] Example 7

[0131] The only difference between Example 7 and Example 1 is that in the preparation of the hard carbon material, in step S2, the mass ratio of porous carbon to thermosetting phenolic resin is 1:0.05, and the other conditions remain the same as in Example 1.

[0132] Example 8

[0133] The only difference between Example 8 and Example 1 is that in the preparation of the hard carbon material, in step S2, the mass ratio of porous carbon to thermosetting phenolic resin is 1:0.30, and the other conditions remain the same as in Example 1.

[0134] Example 9

[0135] The only difference between Example 9 and Example 1 is that in the preparation of the hard carbon material, in step S2, the mass ratio of porous carbon to thermosetting phenolic resin is 1:0.25, and the other conditions remain the same as in Example 1.

[0136] Example 10

[0137] The only difference between Example 10 and Example 1 is that in the preparation of the hard carbon material, in step S1-1, the mass ratio of the biomass carbon source to the mixed molten salt is 1:1, and the other conditions remain the same as in Example 1.

[0138] Embodiment 11

[0139] The only difference between Example 11 and Example 1 is that in the preparation of the hard carbon material, in step S1-1, the mass ratio of the biomass carbon source to the mixed molten salt is 1:30, and the other conditions remain the same as in Example 1.

[0140] Example 12

[0141] The only difference between Example 12 and Example 1 is that in the preparation of the hard carbon material, in step S1-1, the mass ratio of the biomass carbon source to the mixed molten salt is 1:15, and the other conditions remain the same as in Example 1.

[0142] Embodiment 13

[0143] The only difference between Example 13 and Example 1 is that in the preparation of the hard carbon material, in step S1-1, the mass ratio of the biomass carbon source to the mixed molten salt is 1:20, and the other conditions remain the same as in Example 1.

[0144] Embodiment 14

[0145] The only difference between Example 14 and Example 1 is that in the preparation of the hard carbon material, in step S1-1, the mass ratio of the biomass carbon source to the mixed molten salt is 1:5, and the other conditions remain the same as in Example 1.

[0146] Comparative Example 1

[0147] (1) Preparation of hard carbon materials:

[0148] S0, soaking the biomass coconut shell raw material in deionized water, mechanically stirring for 2 hours to wash to remove dust adsorbed on the surface, and then performing solid-liquid separation on the above-mentioned feed liquid by normal pressure filtration, placing the obtained solid coconut shell filter cake material in a blast dryer at 105° C. and drying it for 12 hours, and after drying, crushing the obtained coconut shell material by a jet mill to obtain crushed coconut shell;

[0149] S1. Place the crushed coconut shell in a carbonization furnace, and under nitrogen protection, heat the temperature to 700°C at a rate of 2°C / min and keep it at that temperature for 3 h for pre-carbonization. After the temperature naturally cools to room temperature, discharge the material to obtain porous carbon;

[0150] S2, mixing porous carbon and thermosetting phenolic resin (residual carbon value 23%, viscosity 35 cp) in a mass ratio of 1:0.15 in a fusion machine at a speed of 300 r / min for 30 min to obtain a hard carbon precursor;

[0151] S3. Place the hard carbon precursor in a carbonization furnace. Under nitrogen protection, heat the temperature to 700°C at a rate of 3°C / min and keep it for 2 h. Then heat the temperature to 1400°C at a rate of 2°C / min and keep it for 2 h for carbonization. After naturally cooling to room temperature, discharge the material to obtain the hard carbon material.

[0152] (2) Preparation of sodium ion battery: The specific steps are the same as those in Example 1.

[0153] Comparative Example 2

[0154] (1) Preparation of hard carbon materials:

[0155] S0, soaking the biomass coconut shell raw material in deionized water, mechanically stirring for 2 hours to wash to remove dust adsorbed on the surface, and then performing solid-liquid separation on the above-mentioned feed liquid by normal pressure filtration, placing the obtained solid coconut shell filter cake material in a blast dryer at 105 ° C for 12 hours, and after drying, crushing the obtained coconut shell material by a jet mill to obtain crushed coconut shell;

[0156] S1-1, according to the mass ratio of crushed coconut shell to mixed molten salt being 1:10, crushed coconut shell and lithium chloride / potassium chloride mixed molten salt (molar ratio being 1:0.7) were mixed by ball mill at 400 r / min for 2 h to obtain a mixture;

[0157] S1-2, placing the above-mentioned mixed material in a carbonization furnace, under nitrogen protection conditions, heating the temperature to 700°C at a rate of 2°C / min and keeping it warm for 3 hours for pre-carbonization, discharging the material after it naturally cools down to room temperature, and then soaking the material in deionized water, mechanically stirring for 2 hours to wash to remove the molten salt, and obtaining a liquid feed; then the liquid feed is subjected to solid-liquid separation by normal pressure filtration, and the obtained precursor filter cake material is placed in a blast dryer and dried at 105°C for 12 hours to obtain porous carbon; the obtained filtrate is subjected to solution evaporation under the conditions of an absolute pressure of 30 kPa and an evaporation temperature of 70°C, and the obtained solid is the recovered molten salt;

[0158] S2. Place the porous carbon in a carbonization furnace. Under nitrogen protection, heat the temperature to 700°C at a rate of 3°C / min and keep it for 2 h. Then heat the temperature to 1400°C at a rate of 2°C / min and keep it for 2 h for carbonization. After naturally cooling to room temperature, discharge the material to obtain a hard carbon material.

[0159] (2) Preparation of sodium ion battery: The specific steps are the same as those in Example 1.

[0160] Comparative Example 3

[0161] The difference between this comparative example and Example 1 is that in the preparation of the hard carbon material, in step S1-1, only potassium chloride is used to replace the mixed molten salt, and the other conditions are consistent with Example 1.

[0162] Comparative Example 4

[0163] The difference between this comparative example and Example 1 is that in the preparation of the hard carbon material, in step S2, the mass ratio of the porous carbon to the thermosetting phenolic resin is 1:0.02, and the other conditions are the same as those in Example 1.

[0164] Comparative Example 5

[0165] The difference between this comparative example and Example 1 is that in the preparation of the hard carbon material, in step S2, the mass ratio of the porous carbon to the thermosetting phenolic resin is 1:0.5, and the other conditions remain the same as in Example 1.

[0166] Comparative Example 6

[0167] The difference between this comparative example and Example 1 is that in the preparation of the hard carbon material, in step S1-1, the mass ratio of the biomass carbon source to the mixed molten salt is 1:35, and the other conditions are consistent with Example 1.

[0168] Comparative Example 7

[0169] The difference between this comparative example and Example 1 is that in the preparation of the hard carbon material, in step S1-1, the mass ratio of the biomass carbon source to the mixed molten salt is 1:0.5, and the other conditions are consistent with Example 1.

[0170] Effect Example 1

[0171] The porous carbon and hard carbon materials obtained in Examples 1-14 and Comparative Examples 1-7 were subjected to the following characterization and testing:

[0172] (1) Characterization of specific surface area and pore structure: The specific surface area and pore structure were measured using an American Micromeritics fully automatic adsorption and desorption instrument (model ASAP2460). The specific surface area test adsorbent was nitrogen, the measurement temperature was 77 K, and it was calculated by the BET method; the micropore size test adsorbent was carbon dioxide, the measurement temperature was 273 K, the powder degassing temperature was 300 ° C, the relative pressure range P / P0 was 0-1, and it was analyzed by the DFT model. The relevant test results are shown in Table 1. Among them, the pore size distribution diagram of the hard carbon material in Example 1 is shown in Table 1. Figure 1 shown.

[0173] (2) D50 particle size test: The particle size was measured by laser diffractometer (Mastersize 2000, Malvern 2000). The test results are shown in Table 1.

[0174] (3) True density: The true density of hard carbon materials was measured using the American Quantachrome UltraPYC1200e fully automatic true density analyzer and is denoted as ρ 真密度 .

[0175] Closed pore volume (V 闭孔 ) is calculated as: V 闭孔 =(1 / ρ 真密度 )-(1 / 2.26).

[0176] The specific data of true density and closed pore volume are shown in Table 1.

[0177] (4) Tap density: The tap density of the hard carbon material was measured by tapping method using a tap density tester FZS4-4B. The test results are shown in Table 1.

[0178] Effect Example 2

[0179] The porous carbon and hard carbon materials obtained in Example 1 were characterized by SEM morphology: a Zeiss ZEISS scanning electron microscope (model Sigma500) was used for testing at a test voltage of 1.00 KV. The SEM images obtained were as follows: Figure 2 and Figure 3 shown.

[0180] Effect Example 3

[0181] The capacity and initial efficiency of the sodium ion batteries obtained in Examples 1-14 and Comparative Examples 1-7 were tested:

[0182] The assembled sodium-ion battery was left at room temperature for 24 hours before the electrochemical test began. Constant current charge and discharge experiments were performed on the LAND battery test system (model CT2001A), with a charge and discharge voltage window of 0-2.0 V and a charge and discharge rate of 0.1C. The discharge capacity and charge capacity were measured, and the first efficiency = charge capacity / discharge capacity × 100%.

[0183] The test results are shown in Table 2.

[0184]

[0185]

[0186] According to Table 1 and Table 2, the average pore size of the hard carbon materials prepared in Examples 1-14 of the present invention can reach 1.93-2.20 nm, and the true density can reach 1.29-1.37 g / cm 3 , the tap density can reach 0.73-0.80g / cm 3 , the closed pore volume can reach 0.287-0.333 cm 3 / g, with a specific surface area of ​​2.1-4.7 m 2 / g. The charging capacity of the sodium-ion battery containing it can reach more than 330 mAh / g, or even more than 370 mAh / g; and it can also take into account the excellent first efficiency, which can be more than 88.8%.

[0187] In Examples 1-14 of the present invention, a mixed molten salt is used to form pores in the biomass carbon source, and then a coating agent is used for surface coating treatment, and a hard carbon material is obtained by carbonization treatment. When no binary molten salt is used, only a single molten salt is used, the amount of the mixed molten salt is too small, the amount of the coating agent is too small, or no surface coating is performed, both high charging capacity and excellent first efficiency cannot be taken into account.

[0188] Compared with Example 1, it can be seen that no molten salt is used in Comparative Example 1, and a single molten salt is used instead of a mixed molten salt in Comparative Example 3. The first effect of the obtained sodium ion battery is deteriorated, and the charging capacity is significantly reduced, and both high charging capacity and excellent first effect cannot be taken into account. This may be because the introduction of molten salt has a significant effect on the pore structure and specific surface area of ​​the hard carbon precursor. The molten salt plays a dual role as a heat transfer medium and a template. During the pre-carbonization process, the violent thermal motion of the molten salt fluid will erode the carbon surface. At the same time, the molten salt can diffuse and embed into the carbon structure, thereby inducing the generation of pores as a template. If a single molten salt is used, due to the high melting point of a single chloride salt, the molten salt only plays the role of a solid sealant during the carbonization process, and the template effect is not fully utilized, so it does not play a significant role in the regulation of the precursor structure, and the resulting hard carbon material has fewer closed pores. However, when a mixed molten salt is used, a minimum eutectic melting point can be formed, which can act as a liquid sealant to isolate the air and produce a porous structure as a template.

[0189] Compared with Example 1, it can be seen that in Comparative Example 2, no coating agent is used to coat the porous carbon surface, and the initial efficiency and charging capacity of the obtained sodium ion battery are significantly deteriorated. This may be because when only carbonization treatment is performed without surface coating treatment, the obtained hard carbon material has a higher specific surface area, and too much SEI film will be formed on the surface of the hard carbon material in the sodium battery test.

[0190] Compared with Example 1, it can be seen that in Comparative Examples 4 and 5, the mass ratio of porous carbon to thermosetting phenolic resin is too large or too small, and the relative amount of the corresponding coating agent is too small or too much, and the initial efficiency and charging capacity of the obtained sodium ion battery are significantly deteriorated. This may be because the relative amount of the coating agent is too small, and the defects of the porous carbon cannot be effectively modified; the relative amount of the coating agent is too much, which will introduce more new defects.

[0191] Compared with Example 1, it can be seen that when the mass ratio of the biomass carbon source to the mixed molten salt in Comparative Examples 6 and 7 is too small or too large, and the relative amount of the corresponding mixed molten salt is too small, the first effect of the obtained sodium ion battery is reduced and the charging capacity is significantly deteriorated. This may be because when the relative amount of the mixed molten salt is too small, the etching effect on the biomass carbon source is weak and more pore structures cannot be formed. When the relative amount of the mixed molten salt is too much, the biomass carbon source is over-etched, and all defects cannot be effectively modified when coated under the same conditions.

[0192] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A method for preparing a hard carbon material, characterized in that: It includes the following steps: S1. Mixing a biomass carbon source and a mixed molten salt to obtain a mixture, and heat-treating the mixture to obtain porous carbon; wherein the mass ratio of the biomass carbon source to the mixed molten salt is 1:(1-30); and the mixed molten salt contains at least two molten salts; S2, using a coating agent to perform surface coating treatment on the porous carbon to obtain a hard carbon precursor; wherein the mass ratio of the porous carbon to the coating agent is 1: (0.05-0.3); S3, carbonizing the hard carbon precursor to obtain a hard carbon material.

2. The method for preparing a hard carbon material according to claim 1, characterized in that: In step S1, the porous carbon satisfies one or more of the following conditions ae: a. In step S1, the specific surface area of ​​the porous carbon is 100-1500 m 2 / g, preferably 200~1000 m 2 / g, for example, 328.4 m 2 / g, 389.3 m 2 / g, 420.6 m 2 / g, 455.7 m 2 / g, 489.6 m 2 / g or 620.5 m 2 / g; b. In step S1, the micropore specific surface area of ​​the porous carbon is 50-600 m 2 / g, preferably 100~500 m 2 / g, for example 257.2 m 2 / g, 316.3 m 2 / g, 323.4 m 2 / g, 350.6 m 2 / g, 405.4 m 2 / g or 480.8 m 2 / g; c. In step S1, the micropore volume of the porous carbon is 0.10-0.60 cm 3 / g, preferably 0.10~0.5 cm 3 / g, for example 0.20 cm 3 / g, 0.24cm 3 / g, 0.25 cm 3 / g, 0.28cm 3 / g, 0.30 cm 3 / g or 0.35cm 3 / g; d. In step S1, the average pore size of the porous carbon is 1.50-3.0 nm, preferably 2.0-2.5 nm, for example, 2.13 nm, 2.17 nm, 2.18 nm, 2.25 nm, 2.27 nm or 2.38 nm; e. In step S1, the tap density of the porous carbon is 0.25-0.70 g / cm 3 , preferably 0.30~0.60 g / cm 3 , for example 0.38 g / cm 3 , 0.44 g / cm 3 , 0.47 g / cm 3 , 0.50 g / cm 3 , 0.51 g / cm 3 or 0.55 g / cm 3 .

3. The method for preparing a hard carbon material according to claim 1, characterized in that: Step S1 satisfies one or more of the following conditions ah: a. In step S1, the biomass carbon source is selected from one or more of coconut shells, walnut shells, fruit shells, coffee grounds, sawdust, lignin, tea stems and bamboo, such as coconut shells; b. In step S1, the mixed molten salt is selected from at least two of lithium chloride, sodium chloride, potassium chloride, cesium chloride, calcium chloride and magnesium chloride; for example, sodium chloride / potassium chloride, calcium chloride / sodium chloride, potassium chloride / lithium chloride or sodium chloride / cesium chloride; c. In step S1, the mass ratio of the biomass carbon source to the mixed molten salt is 1:(5-30), for example, 1:10 or 1:20; d. In step S1, before the mixing, the biomass carbon source is also pretreated; preferably, the pretreatment step includes washing, drying and crushing; e. In step S1, the mixing device is a ball mill; wherein the rotation speed of the ball mill is preferably 300-800 r / min, for example, 400 r / min, 450 r / min or 500 r / min; the ball milling time of the ball mill is preferably 0.5-10 h, for example, 0.5 h, 1 h or 2 h; f. In step S1, the heat treatment further includes washing and drying; g. Step S1, the heat treatment is carried out by pre-carbonization; Wherein, the pre-carbonization temperature is preferably 400-800°C, such as 600°C, 700°C or 800°C; Wherein, the pre-carbonization time is preferably 1 to 5 hours, such as 2 hours, 3 hours or 4 hours; Wherein, the heating rate of the pre-carbonization is preferably 1-5°C / min, for example, 2°C / min, 3°C / min or 5°C / min; h. In step S1, the heat treatment is performed under an inert atmosphere; wherein the inert atmosphere preferably includes an inert gas and / or nitrogen, such as nitrogen; the inert gas is, for example, argon.

4. The method for preparing a hard carbon material according to claim 1, characterized in that: In step S1, the mixed molten salt includes molten salt A and molten salt B; the molten salt A is lithium chloride, sodium chloride or calcium chloride; the molten salt B is potassium chloride or sodium chloride; the molten salt A and the molten salt B are of different types; The molar ratio of the molten salt A to the molten salt B is preferably 1:(0.2-5), more preferably 1:(0.5-5), for example 1:0.7, 1:1 or 1:

2.

5. The method for preparing a hard carbon material according to claim 1, characterized in that: Step S2 satisfies one or more of the following conditions ac: a. In step S2, the mass ratio of the porous carbon to the coating agent is 1:(0.15-0.3), for example, 1:0.20 or 1:0.25; b. In step S2, the surface coating treatment comprises the following steps: mixing the coating agent with the porous carbon; wherein the mixing is preferably carried out in a fusion machine; wherein the rotation speed of the fusion machine is preferably 200 to 800 r / min, for example, 300 r / min, 350 r / min or 400 r / min; c. In step S2, the coating agent includes one or more of phenolic resin, epoxy resin, petroleum resin and polyester resin, preferably phenolic resin; wherein the phenolic resin preferably includes thermosetting phenolic resin and / or thermoplastic phenolic resin; Preferably, the thermosetting phenolic resin is a liquid, and the thermosetting phenolic resin meets the following conditions: viscosity of 20-50 cp, moisture content ≤0.5%, ash content ≤0.1%, residual carbon value of 15%-30%, free phenol content ≤1.5%, and the percentage is the mass percentage of the thermosetting phenolic resin; Preferably, when the thermoplastic phenolic resin is solid, the method further comprises mixing the thermoplastic phenolic resin and a solvent to form a liquid mixture; wherein the solvent is preferably one or more of an alcohol solvent, a ketone solvent and a benzene solvent, and more preferably an alcohol solvent; the alcohol solvent is, for example, an ethanol solvent; wherein the mass ratio of the thermoplastic phenolic resin to the solvent is preferably (0.1-2):1, for example, 0.2:1 or 0.3:1; Wherein, the thermoplastic phenolic resin is preferably a linear phenolic resin; the linear phenolic resin is preferably selected from one or more of phenol formaldehyde resin, resorcinol formaldehyde resin, m-aminophenol formaldehyde resin, phenolic epoxy resin and benzoxazine resin, for example, phenol formaldehyde resin; The thermoplastic phenolic resin preferably meets the following conditions: softening point of 80-120° C., ash content ≤0.1%, moisture content ≤0.5%, residual carbon value 40%-70%, where the percentages are the mass percentages of the thermoplastic phenolic resin.

6. The method for preparing a hard carbon material according to claim 1, characterized in that: In step S3, the carbonization treatment satisfies one or more of the following conditions af: a. In step S3, the temperature of the carbonization treatment is 1100-1500° C., for example, 1200° C., 1300° C. or 1400° C.; b. In step S3, the carbonization treatment time is 1 to 4 hours, for example, 2 hours, 3 hours or 4 hours; c. In step S3, the heating rate of the carbonization treatment is 1-10°C / min, preferably 1°C / min, 2°C / min, 3°C / min or 5°C / min; d. In step S3, the carbonization treatment is performed under an inert atmosphere; wherein the inert atmosphere preferably includes an inert gas and / or nitrogen, such as nitrogen; the inert gas is, for example, argon; e. In step S3, the carbonization treatment is carried out by a staged heating method; the staged heating method preferably includes the following steps: firstly heating to 500-700°C at a heating rate of 2-10°C / min, maintaining the temperature for 1-4 hours, and then heating to 1100-1500°C at a heating rate of 1-5°C / min, maintaining the temperature for 1-4 hours; f. In step S3, the equipment for carbonization treatment is a pit furnace, a rotary kiln, a tubular furnace, a box furnace, a tunnel kiln, a vacuum furnace, a push plate kiln or a roller kiln.

7. A hard carbon material, characterized in that: The hard carbon material is prepared by the method for preparing the hard carbon material according to any one of claims 1 to 6.

8. The hard carbon material according to claim 7, characterized in that It meets one or more of the following conditions: a. The specific surface area of ​​the hard carbon material is 1 to 20 m 2 / g, preferably 2~10 m 2 / g, for example 2.5 m 2 / g, 3.0 m 2 / g, 3.4 m 2 / g, 3.7 m 2 / g, 3.9 m 2 / g or 4.7 m 2 / g; b. The average pore size of the hard carbon material is 0.3-1.5 nm, preferably 0.4-1.0 nm, for example 0.53 nm or 0.88 nm; c. The median particle size Dv50 of the hard carbon material is 4 to 10 μm, preferably 5 to 7 μm, for example 5.4 μm, 5.6 μm, 5.7 μm, 6.0 μm or 6.1 μm; d. The true density of the hard carbon material is 1.30-1.50 g / cm 3 , for example 1.31 g / cm 3 , 1.32 g / cm 3 , 1.33 g / cm 3 , 1.34g / cm 3 , 1.35 g / cm 3 or 1.36 g / cm 3 ; e. The tap density of the hard carbon material is 0.5-0.9 g / cm 3 , preferably 0.6~0.8 g / cm 3 , for example 0.74 g / cm 3 , 0.76g / cm 3 , 0.77 g / cm 3 , 0.78 g / cm 3 or 0.80 g / cm 3 ; f. The closed pore volume of the hard carbon material is 0.27-0.35 cm 3 / g, for example, 0.287 cm 3 / g, 0.293 cm 3 / g, 0.298 cm 3 / g, 0.304 cm 3 / g, 0.309 cm 3 / g, 0.315 cm 3 / g, 0.321 cm 3 / g, 0.327 cm 3 / g or 0.333cm 3 / g; g. The hard carbon material comprises a porous carbon core, and amorphous carbon is arranged on the surface and in the pores of the porous carbon core.

9. Use of the hard carbon material as claimed in claim 7 or 8 as a negative electrode material in a sodium ion battery.

10. A sodium ion battery, characterized in that: It comprises the hard carbon material as claimed in claim 7 or 8.

Citation Information

Patent Citations

  • Method for preparing coal pitch-based activated porous carbon through melting and alkali activation of chlorate mixture

    CN111232973A

  • Hard carbon negative electrode material, preparation method thereof, pole piece containing hard carbon negative electrode material and lithium ion battery

    CN111864206A

  • Preparation method of hard carbon negative electrode material for sodium ion battery and sodium ion battery

    CN118125419A

  • Preparation method and application of molten salt template assisted bituminous coal-based high-temperature carbonized hard carbon negative electrode

    CN118666266A

  • Preparation method of porous high-capacity biomass hard carbon negative electrode material of sodium-ion battery

    CN118929634A

Cited By

  • Method for preparing sodium-ion battery negative electrode material by regulating and controlling hard carbon structure through chemical treatment of biomass precursor

    CN120646803A

  • Preparation method of biomass hard carbon material, biomass hard carbon material and application of biomass hard carbon material

    CN121449042A

  • Method for preparing biomass hard carbon material, biomass hard carbon material and application thereof

    CN121449042B

  • Preparation method and equipment of phenolic resin-based carbonaceous porous material with walnut shell structure and rich in micropores and application of phenolic resin-based carbonaceous porous material

    CN121609334A